2015
DOI: 10.1007/s11663-015-0441-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Static Magnetic Field on Recalescence and Surface Velocity Field in Electromagnetically Levitated Molten CuCo Droplet in Undercooled State

Abstract: TSUBASA KITAHARA, KOKI TANADA, SHOYA UENO, KEN-ICHI SUGIOKA, MASAKI KUBO, TAKAO TSUKADA, MASAHITO UCHIKOSHI, and HIROYUKI FUKUYAMA The recalescence events of phase-separated Co-rich phases in undercooled molten CuCo droplets electromagnetically levitated under various static magnetic fields were observed directly using a high-speed camera, and also the surface velocities on the levitated droplets were measured by tracing the trajectories of the phase-separated Co-rich phases as tracer particles. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The influence of the static magnetic fields on the metastable liquid phase separation in the glass-fluxed Cu-Co samples exhibits similarities and differences compared to those observed for electromagnetically levitated samples [40][41][42][43][44]. The similarities are seen in the sphere-like morphology and the monomodal size distribution of the Co-rich droplets frozen in at lower intensities or smaller gradients of the magnetic fields.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The influence of the static magnetic fields on the metastable liquid phase separation in the glass-fluxed Cu-Co samples exhibits similarities and differences compared to those observed for electromagnetically levitated samples [40][41][42][43][44]. The similarities are seen in the sphere-like morphology and the monomodal size distribution of the Co-rich droplets frozen in at lower intensities or smaller gradients of the magnetic fields.…”
Section: Discussionmentioning
confidence: 67%
“…Recent studies by Zhang and colleagues [40][41][42] showed that imposition of static magnetic fields on electromagnetically levitated Cu-Co alloys damped forced convection and brought about a microgravity-like effect on the droplet size distribution. Such a magnetic field effect was observed also by Sugioka and colleagues [43,44]. Compared to parabolic flights or space experiments, ground-based experiments with the use of static magnetic fields are cheap and offer a new opportunity for studies of liquid phase separation in undercooled Cu-Co and other Cu-based alloys.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…In microgravity, Bojarevics et al [163] performed a numerical simulation on the melting of silicon droplets in an AC+DC magnetic field and presented the typical temperature and velocity field. The stable droplet suspension helped in studying heat transfer in microgravity environments [164], ensuring demanding chemical reactions without bacterial and virus pollution, smelting high-purity materials [165], promoting the fusion of incompatible alloys [166] and optimizing the welding effect [167].…”
Section: Discussionmentioning
confidence: 99%